The art and craft of designing a logo - Takács, Ágnes; Balázs, Áron; Tóth, Áron (Design of Machines and Structures, 2025)
This article provides insight into the logo design process. The aim of the authors is to explore a generally applicable design process through literature research, and then to present the proposed design process with the help of case studies. The publication also covers how image-generating artificial intelligence can support designer thinking and designer work.